Association Between Procrastination And Academic Stress In Peruvian Second-Year Medical Students - León, Eduardo Orco (2022)
Introduction: University medical students are a population exposed to a high academic load, high level of exigency, high demand of time and there are factors that can affect the effectiveness of academic performance, such as stress and procrastination. Objective: Evaluate the association between stress and procrastination in a pilot sample of medical students at a university in Lima, Peru. Material and methods: A cross-sectional analytical study was conducted, where medical students from the Research Methodology course were recruited at a university in the Peruvian capital. In them, stress and procrastination were measured, both with previously validated tests, then these variables were related and adjusted according to their sex and age. For analytical statistics, generalized linear models were used and p-values ≤ 0.05 were considered statistically significant. Results: When performing the multivariate analysis, it was found that there was a relationship between procrastination and male gender (p = 0.001), age (p = 0.035) and stress (p = 0.022) of the respondents. Conclusions: Procrastination maintains in the sample studied an important association with the stress that students have, as well as with their gender and age.